An Interracial Movement of the Poor : Community Organizing and the New Left in the 1960s. - Frost, Jennifer (NYU Press, 2001)
Choice Outstanding Academic Title 2002. Community organizing became an integral part of the activist repertoire of the New Left in the 1960s. Students for a Democratic Society, the organization that came to be seen as synonymous with the white New Left, began community organizing in 1963, hoping to build an interracial movement of the poor through which to demand social and political change. SDS sought nothing less than to abolish poverty and extend democratic participation in America. Over the next five years, organizers established a strong presence in numerous low-income, racially diverse u.